2008
DOI: 10.1111/j.1530-0277.2008.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Topiramate or Naltrexone for the Treatment of Alcohol‐Dependent Patients

Abstract: Both topiramate and naltrexone were efficacious in the treatment of alcohol dependence, and the treatment costs were similar. There is a trend for topiramate to be superior to naltrexone on critical measures of drinking; however, the study did not have adequate statistical power to establish this fact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 52 publications
2
39
0
1
Order By: Relevance
“…Topiramate has also been studied in longer prospective designs [94] and, in comparison to other medications approved for alcohol dependence including disulfiram [97] and naltrexone, topiramate demonstrated non-inferiority and even superiority in selected studies [98100]. Due to topiramate's high side effect burden at higher doses, it is critical to determine the optimal dose range for balancing relapse prevention/harm reduction with decreased risk for adverse effects [101].…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…Topiramate has also been studied in longer prospective designs [94] and, in comparison to other medications approved for alcohol dependence including disulfiram [97] and naltrexone, topiramate demonstrated non-inferiority and even superiority in selected studies [98100]. Due to topiramate's high side effect burden at higher doses, it is critical to determine the optimal dose range for balancing relapse prevention/harm reduction with decreased risk for adverse effects [101].…”
Section: Anticonvulsants For the Treatment Of Harmful Drinking Pattmentioning
confidence: 99%
“…Other recent studies comparing TP with naltrexone found that both drugs were similarly efficacious in improving alcohol use parameters. 5,6 Despite considerable interest in TP as a promising drug for alcohol dependence, the mechanisms by which this medication reduces drinking remain to be characterized. Pharmacological strategies for treating alcoholism generally aim at alleviating withdrawal symptoms, reducing craving or the urge to drink, attenuating the pleasurable effects of alcohol ingestion, and intensifying the unpleasant effects of alcohol use.…”
mentioning
confidence: 99%
“…A total of eight studies reported on the course of employmentrelated difficulties. Five of these studies reported improvement [68], while two studies reported improvement/stability [69,29], The most frequent determinants for positive evolution were treatment interventions (reported by five different studies), including two pharmacotherapies [68,70], and improvement in drinking status (reported by three studies). Treatment in general was considered a positive determinant in three studies [20].…”
Section: R Em Unerative Em P Lo Ym E N T (D850)mentioning
confidence: 94%